A Systematic Scoping Review Of Malaria Prevention Programs In Pregnancy - Dewa Ayu Putu Mariana Kencanawati; Ignasensia Dua Mirong; Evi Martha (Syntax Corporation Indonesia, 2022)
There are few guidelines for health workers to follow when providing and managing malaria prevention therapy during pregnancy, but due to a lack of effective treatment options, malaria management during pregnancy has become non-standard in many countries. This study aims to assess the malaria prevention program in pregnancy, including its advantages, challenges, and obstacles. It was carried out using a systematic scoping review of the literature to identify publications that addressed the prevention program. A structured search was conducted on different databases using predefined eligibility criteria for the 17 selected articles. Malaria prevention programs in pregnancy are effective, but they must be integrated and involve the community. Various countries are having difficulty implementing WHO-recommended strategies, such as Long-Lasting Insecticide Nets (LLINs), antimalarial drugs, and Rapid Diagnostic Tests. Therefore it is necessary to develop an integrated program to prevent and treat malaria in pregnancy.